(untitled) (Research Journal of Mathematics & Technology, 2022)
Although Vietnamese secondary students are quite good in solving problems with given mathematical models or partial modelling, but they feel difficult in creating their own mathematical models to solve non-routine realistic problems. Influenced by a focus on modelling with computer-based mathematical tools (CBMT), we will try to describe and give some situations that involved Vietnamese students in setting up and using models to solve real-world problems. We introduced the cycle of modelling with exponential and sinusoidal functions by using Microsoft Excel (2007) and GSP (version 5) as computer-based mathematical tools. In this article, we use Microsoft Excel as an automatically CBMT to set up exponential model, and the GSP as dynamically CBMT to make sinusoidal model. The results showed that setting up models with CBMT created an active learning environment in the mathematics classrooms and secondary students to construct a specific cycle with some concrete steps to solve real-life problems.